EFEKTIVITAS PROGRAM JAKSA MASUK SEKOLAH (JMS) DALAM UPAYA MENINGKATKAN KESADARAN HUKUM SISWA SEKOLAH MENENGAH PERTAMA (SMP) DI KABUPATEN BADUNG - Astari Dewi, Ni Kadek Ayu; Yudartha, I Putu Dharmanu; Purnamaingsih, Putu Eka (CITIZEN CHARTER, 2021)
The Attorney Goes to School Program (JMS) is a non-Penal policy program from the Indonesian Attorney General's Office which aims to increase legal awareness to the public. The purpose of this research is to see the effectiveness of the implementation of the JMS Program in increasing the legal awareness of students in Badung Regency. Data collection was carried out by interview, observation, and documentation methods. The research was studied using Duncan's Theory of Effectiveness with indicators of Achievement of Goals, Integration, and Adaptation. The results showed that the implementation of the JMS program in Badung Regency was running quite effectively and was running optimally. The JMS program has succeeded in implementing plans and adaptations but still does not meet the Integration indicator because the Badung District Prosecutor's Office is still facing a shortage of human resources, and has not socialized the program to schools in Badung Regency. Keywords: Effectiveness, Public Policy, and Legal Awareness